Inclusive pedagogy across the curriculum - Deppeler, Joanne, 1951- (International perspectives on inclusive education ;, 2015)
This volume focuses on an inclusive pedagogical approach for enhancing teaching and learning in key areas of curriculum including: literacy, mathematics, science, social studies, and the arts. In the introductory chapters, the concept of inclusive pedagogy is framed in relation to the actions of teachers in providing quality teaching and learning experiences for everyone in inclusive classrooms. Unlike much of what has previously occurred in inclusive practice the approach does not differentiate by providing alternative teaching and learning for students who are different. Focusing on what is to be learned in a particular subject area, the intention is to avoid the issues associated with defining some learners as different. - Resumé vydavatel